Thermal Computational Fluid Dynamics Simulation of Two Designs of Direct Dehydrators for Agricultural Products - Said Arturo Rodríguez-Romero; Manuel Toledano-Ayala; Gonzalo Macías-Bobadilla; Edgar Alejandro Rivas-Araiza; Priscila Sarai Flores-Aguilar; Genaro Martín Soto-Zarazúa (Applied Sciences)
The dehydration process modifies the physical and chemical characteristics of certain crops, thereby increasing their shelf life and consequently reducing the organic waste generated. This process is contingent upon maintaining optimal temperature and humidity levels to prevent deterioration of the product. As indirect dehydrators have a high energy demand, new designs are required that facilitate the uniform distribution of air with a high-volume capacity of 100 kg per day. In the present study, computational fluid dynamics (CFD) techniques were employed to assess the drying performance of two dehydrator models. The simulations were executed in Solidworks 2020 and Flow Simulation, and they examined temperature distribution and velocity within the interior of the dehydrators. In Model 1, an inlet volume flow of 0.08 m3 s−1 and a heat source of 3.5 kW are considered, within a volume of 2.11 m3. In Model 2, an inlet volume flow of 0.03 m3 s−1 and two heat source of 2.5 kW are considered, within a volume of 2.02 m3. Model 1 was unable to achieve uniform air distribution within the drying chamber. In contrast, Model 2 demonstrated uniform velocity and temperature across the majority of the drying chamber, making it a superior option.